2015
DOI: 10.1080/19443994.2015.1054886
|View full text |Cite
|
Sign up to set email alerts
|

Removal of reactive magenta-MB from aqueous solution by persulphate-based advanced oxidation process

Abstract: In this study, the possibility of removing magenta-MB by persulphate (PS)-based advanced oxidation process has been evaluated. PS was activated by chemical means with the use of ferrous ion to produce sulphate radical (SO Å 4 ). Experiments were conducted in batch mode. The effect of operational parameters such as PS dosage (varied from 40 to 140 mg/L), ferrous ion dosage (varied from 0 to 100 mg/L), pH (both acidic and basic) and contact time were studied. For an initial dye concentration of 100 mg/L, maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 46 publications
(88 reference statements)
3
6
0
Order By: Relevance
“…49 The rate of the second scavenging reaction was higher than the rst one, which indicates that the more signicant scavenging was due to the reaction between sulphate radicals. 50 Similar results were observed by Sarath et al 38 for magenta MB degradation.…”
Section: Effect Of Hydrogen Peroxide Concentration On the Performance...supporting
confidence: 82%
See 1 more Smart Citation
“…49 The rate of the second scavenging reaction was higher than the rst one, which indicates that the more signicant scavenging was due to the reaction between sulphate radicals. 50 Similar results were observed by Sarath et al 38 for magenta MB degradation.…”
Section: Effect Of Hydrogen Peroxide Concentration On the Performance...supporting
confidence: 82%
“…This removal is mainly by the persulphate anions present in water. In a similar way, less than 10% of magenta-MB dye removal was observed by Sarath et al 38 These insignicant removal efficiencies of persulphate indicate the signicance of activation in persulphate based advanced oxidation processes. When IAC was present in water, about 50% of dye was removed from the aqueous solution aer 15 min, indicating that adsorption of dye took place more quickly on the active sites of IAC.…”
Section: Catalytic Activity Of Iacsupporting
confidence: 76%
“…At pH 2 higher amount of proton present in form of 3 + which decreases effective decomposition of persulfate oxidant while increasing pH, quantity of 3 + ions decreases in solution which leads to effective generation of sulfate radicals from persulfate as in shown in given Eqn. ( 3) & ( 4) (Romero et al, 2010;Sarath et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…6. The increasing amplitude at pH 2, removal of COD increased to 30.8% and on other hand middle level pH 5 with amplitude up to 50% removal efficiency increases further as a result of generation of effective cavitation and effective decomposition of persulfate (Sarath et al, 2016). Further increasing amplitude to 80% at pH 5, reduces removal due to reduced cavitational yield, thus increasing or decreasing amplitude beyond or below 50% under near acidic condition (Thanekar & Gogate, 2019).…”
Section: Effect Of Ph and Amplitude On Cod Removalmentioning
confidence: 95%
“…It is observed that TOC removal rate increases with the reaction time and up to 60 % can be reached within 30 min, indicating that the reactive species generated by PMS activation can effectively convert dye molecules into CO 2 , H 2 O and other harmlessly inorganic substances. Similar TOC removal rate can be achieved with a wide pH range, which is reported by Sarath et al[63]. However, more than 50% of mineralization rate can be seen within 20 min in this work, indicating a higher efficiency.…”
supporting
confidence: 89%